2018
DOI: 10.7567/apex.11.071002
|View full text |Cite
|
Sign up to set email alerts
|

Accurate method for estimating hole trap concentration in n-type GaN via minority carrier transient spectroscopy

Abstract: We propose an analysis method for the accurate estimation of the hole trap (H1, EV + 0.85 eV) concentration in n-type GaN via minority carrier transient spectroscopy (MCTS). The proposed method considers both the hole occupation during a filling (current injection) period and the quick carrier recombination via the hole traps near the depletion layer edge immediately after a reverse bias is applied. The reverse bias voltage dependence of the MCTS spectrum indicates that an accurate trap concentration, as well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 28 publications
0
22
0
Order By: Relevance
“…As shown, one electrically active level is found at EnormalV+0.85 eV, with a capture cross section of 5×1015 cm2. This level is known as H1, and its concentration is 1×1014 cm3, as obtained using the method by Kanagae et al In the following, this method will be applied to H1 only.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…As shown, one electrically active level is found at EnormalV+0.85 eV, with a capture cross section of 5×1015 cm2. This level is known as H1, and its concentration is 1×1014 cm3, as obtained using the method by Kanagae et al In the following, this method will be applied to H1 only.…”
Section: Resultsmentioning
confidence: 96%
“…It was shown that one minority carrier trap is present in the as‐grown material at 0.8 eV above the valence band edge (EnormalV), labeled H1. As it was shown that H1 concentration decreases with the carbon content of the epilayers, its nature has been associated with the carbon substitutional (normalCnormalN) and its concentration was accurately estimated by Kanagae et al Besides H1, another trap labeled H3 was also found at EnormalV+0.25 eV, but no hypothesis on the nature of this trap has been put forward. Coming to the case of particle‐irradiated GaN, if we exclude one study on electron‐irradiated GaN or on proton‐irradiated GaN, nothing is known on the presence of minority carrier traps in implanted material.…”
Section: Introductionmentioning
confidence: 99%
“…For the trap parameters, the energy level below the conduction band and the capture cross section were fixed at 0.6 eV and 5.0 × 10 −15 cm 2 for all GaN layers and the substrate, respectively [36]. Approximately 0.6 eV for the trap's energy level is a common value for the experimental results and is observed for the GaN grown on not only SiC but also GaN substrates [8,9,27,[36][37][38][39][40]. The trap concentration of the channel layer was fixed to be at as low as 1.0 × 10 15 cm −3 [37].…”
Section: Device Structures Of Gan Hemts On Gan Substratesmentioning
confidence: 99%
“…Several studies of MOCVD GaN homoepitaxy have shown low carbon concentrations at mid‐ to low‐10 15 cm −3 according to secondary ion mass spectroscopy (SIMS). [ 24–27 ] Despite tremendous efforts on suppressing C incorporation by tuning growth conditions, such as V/III ratio, growth temperature, and growth pressure, [ 22,24,28–30 ] lowering C concentration while maintaining a fast growth rate remains challenging.…”
Section: Introductionmentioning
confidence: 99%